82.9k views
2 votes
10x - 6 = 6x + 6
i need the answer but i think its 3

User TheWuif
by
5.7k points

1 Answer

1 vote

Answer:

= 3

Explanation:

Add 6 to both sides of the equation 10 − 6 = 6 + 6

10x-6=6x+6 10x−6=6x+6

Simplify Add the numbers Add the numbers again 10 = 6 + 12

Subtract 6 from both sides of the equation

10 = 6 + 12

10−6=6+12−6

Simplify

Combine like terms

Combine like terms again

4 = 12

Divide both sides of the equation by the same term

4=12


(4x)/(4) =
(12)/(4)

Simplify Cancel terms that are in both the numerator and denominator then Divide the numbers.

x = 3

User Istiak Morsalin
by
5.9k points